Students wearing Police uniforms exhibit biased attention towards individuals wearing hoodies - Civile, Ciro; Obhi, Sukhvinder (Frontiers in Psychology, 2017)
Police provide an essential public service and they often operate in difficult circumstances, requiring high-speed cognition. Recent incidents involving apparent profiling and aggressive behavior have led to accusations that the police are sometimes biased. Given that previous research has shown a link between clothing and cognition, we investigated the question of whether the police uniform itself might induce a bias in social attention. To address this question, and using a Canadian university student sample, we assessed whether wearing a police uniform biases attention toward black faces compared to white faces, and low-status individuals compared to high-status individuals. In Experiment 1 (n = 28), participants wore either a police-style uniform or mechanic overalls, and performed a shape categorization task in the presence of a distractor that could be either: a black face, a white face, a person wearing a hoodie (whom we propose will be associated with low SES), or a person wearing a suit (whom we propose will be associated with high SES). Participants wearing the police-style uniform exhibited biased attention, indexed by slower reaction times (RTs), in the presence of low-SES images. In Experiment 2 (n = 28), we confirmed this bias using a modified Dot-Probe task – an alternate measure of attentional bias in which we observed faster RTs to a dot probe that was spatially aligned with a low SES image. Experiment 3 (n = 56) demonstrated that attentional bias towards low-SES targets appears only when participants wear the police-style uniform, and not when they are simply exposed to it – by having it placed on the desk in front of them. Our results demonstrate that wearing a police-style uniform biases attention toward low-SES targets. Thus, wearing a police-style uniform may induce a kind of "status-profiling" in which individuals from low-status groups become salient and capture attention. We note that our results are limited to university students and that it will be important to extend them to members of the community and law-enforcement officers. We discuss how uniforms might exert their effects on cognition by virtue of the power and cultural associations they evoke in the wearer.